Implementação do overall equipment effectiveness (OEE): estudo de caso em um curtume - Oliveira, Vinicius Souza (2022)
In order to attend the demands of the market, companies are increasingly seeking continuous improvements in their processes. Some indicators help in the development of organizations, being fundamental for the reduction of losses and, therefore, increase competitiveness. One of these indicators is the OEE (Overall Equipment Effectiveness), which works simultaneously with availability, performance and quality of what is produced. The OEE is an indicator used as a form of management and continuous improvement of machinery and equipment, useful to identifying losses and reduce production costs. In this context, the objective of the present work is to implement the OEE tool in a leather industry and compare the obtained value with those of world class. Regarding the methodological procedure, the case study was used. The data was collected for all working days of the tannery in the month of February 2022. The results showed that the OEE values found for dryers 1 and 2, 82.9% and 79.7, respectively, are close to reaching those of world class.